Influence of lactation number, year and season of calving on milk productivity of cows - O. Kramarenko; S. Kramarenko (Вісник аграрної науки Причорномор'я, 2022)
The main characteristics of the milk productivity of Holstein dairy cattle differ in different countries due to differences in terrain, management and breeding objectives. At the same time, the manifestation of non-genetic (that is, environmental) factors during milk production, as a rule, mask the real breeding value of animals. The main goal of this study was to analyze the influence of lactation number, year and season of calving on the milk productivity of 238 Holstein cows during a 4-year period (2014-2017). The study was conducted using primary data on the dairy productivity of livestock in the conditions of PJSC Plemzavod Stepnoi of the Kamian-Dnipro district of the Zaporizhia region.The following characteristics were evaluated for each animal: duration of lactation, hope for 305 days of lactation, hope for the entire lactation, fat content and protein content in milk. P. Wood's model was used to approximate lactation curves within each subgroup. All signs of milk productivity were analyzed based on the algorithm of one- or two-factor analysis of variance with fixed factors using the statistical package STATISTICA v. 6.0 (Statsoft Inc.).Lactation number was found to have a significant effect on all milk yield traits that were examined (in all cases: p